PENGARUH MORAL KERJA DAN KOORDINASI TERHADAP KINERJA KARYAWAN PADA PT.WELLING TAPIOKA JAYA, SERDANG BEDAGAI SUMATERA UTARA. - Juwita Sari Dewi Hutagalung (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
The purpose of this study was to find out and analyze the effect of work morale and coordination on Employee Performance at PT.Welling Tapioka Jaya Serdang Bedagai The research method used is exploratory research, where the variable is measured by a Likert scale. The method of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were employees of PT. Welling Tapioka Jaya Serdang Bedagai, amounting to 55 people. Saturated sample withdrawal. In this study the population is relatively small, which is as many as 55 people. Data processing uses SPSS version 23 software, with descriptive analysis and hypothesis testing of multiple regression analysis.The results of the study show that: (1) partially the variable work morale influences the Employee Performance at PT.Welling Tapioka Jaya Serdang Bedagai; (2) partially the coordination variables affect the Employee Performance at PT.Welling Tapioka Jaya Serdang Bedagai; (3) simultaneously there is a positive and significant influence between the variables of work morale and coordination on Employee Performance at PT.Welling Tapioka Jaya Serdang Bedagai